Pengaruh Model Pembelajaran (Project Based Learning) terhadap Peningkatan Kompetensi Konsep Dasar Listrik dan Elektronika Siswa: The Influence of the Learning Model (Project Based Learning) on ??Improving Students' Basic Electrical and Electronic Concept Competence - Elsida Aritonang; Deswidya S Hutauruk (Jurnal Pendidikan Sains dan Komputer, 2026)
This study aims to determine the effect of the Project-Based Learning model on improving the Basic Electrical and Electronics Concept Competence of class XI students at SMK Swasta Raksana Medan. The subjects of this study were selected using a total sampling technique, and the treatment group was selected by random sampling, namely the treatment group with the Project-Based Learning learning model (22 people) and the treatment group with the Conventional learning model (22 people). Research data were collected using the Basic Electrical and Electronics Concept Competence test and analyzed using a two-way difference test with a two-tailed t-test at a significance level of 5%. Based on the results of the study, the average Basic Electrical and Electronics Concept Competence of students taught with the Project-Based Learning learning model was 21.91, with a high tendency level, and the average Basic Electrical and Electronics Concept Competence of students taught with the Conventional learning model was 19.86, with a high tendency level. The results of the analysis requirements test show that the distribution of Basic Electrical and Electronics Concept Competence data taught with the Project Based Learning learning model is normally distributed where L Table 0.1832 > L Count 0.0824 and the Basic Electrical and Electronics Concept Competence data taught with the Conventional learning model is normally distributed where L Table 0.1832 > L Count 0.1370 and both data variances are Homogeneous because F Count 1.37 < F Table 2.08. The results of this study indicate that the Project-Based Learning model and the Conventional learning model yield significantly different outcomes in students' Basic Electrical and Electronics Concept Competence, with t Count = 2.52 > t Table = 2.02.